Impacts of Non-Thermal Plasma on the Structural and Optical Characteristics of Cr:Se Core-Shell Thin Films Synthesized Using Chemical Spray Pyrolysis - Hilmi, Taghreed A.; Al-Ansari, Ramiz A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Over the past few years, there has been a significant focus on studying the synthesis and applications of metal nanoparticles. These tiny particles possess distinct properties that set them apart from bulk metals. Cr:Se core-shell nano thin film has been pre-coated by plasma jets with different concentrations (10:0, 8:2, and 6:4) and deposition by chemical spray pyrolysis. The nano-thin films were analyzed by X-ray diffraction (XRD), ultraviolet-visible spectroscopy(UV), and transmission electron microscopy TEM. This study looks into the structure and optical features of core-shell nanoparticles made with different ratios of chromium and selenium (Cr:Se). The X-ray diffraction patterns confirm the crystalline nature of the nanoparticles and the ratio (6:4). Exposing the best crystalline phase to non-thermal plasma (DBD) results in significant changes in the XRD, transitioning towards a more crystalline phase. Tauc plots show a non-linear trend in direct bandgap energies, meaning the energy gap increased (2.77-3.88 eV), notably increasing. Transmission electron microscopy analysis highlights improved nanoparticle distribution and uniformity. non-thermal plasma ( DBD ) significantly enhances the humidity sensitivity, thereby optimizing the nanoparticles for sensor applications. These findings underscore the potential of Cr:Se nanoparticles for advanced optoelectronic and sensing technologies and various technological applications.